2023
DOI: 10.1039/d2nj05566j
|View full text |Cite
|
Sign up to set email alerts
|

Covalent surface modification of nickel ferrite nanoparticles for electrochemical supercapacitor performance

Abstract: Magnetic nanoparticles play vital roles in diverse applications, due to their high surface-to-volume ratio, tuneable optical, electrical, catalytic, biological, nanofluidic, electrochemical supercapacitor, and data storage applications. However, there is a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The modified NiFe 2 O 4 MNPs showcase strong metal-ligand bonds that eventually assist their overall magnetic and electrochemical behavior. Electrochemical studies showed that the diazonium-functionalized pseudocapacitor electrode exhibits substantially higher specific capacitance (~1279 Fg −1 ) than bare NiFe 2 O 4 and (~82-90%) after 2000 cycles [77].…”
Section: Author Detailsmentioning
confidence: 99%
“…The modified NiFe 2 O 4 MNPs showcase strong metal-ligand bonds that eventually assist their overall magnetic and electrochemical behavior. Electrochemical studies showed that the diazonium-functionalized pseudocapacitor electrode exhibits substantially higher specific capacitance (~1279 Fg −1 ) than bare NiFe 2 O 4 and (~82-90%) after 2000 cycles [77].…”
Section: Author Detailsmentioning
confidence: 99%
“…Furthermore, surface engineering techniques are being explored to address challenges in emerging energy storage and conversion technologies. For instance, in the field of electrochemical energy storage, such as supercapacitors [148] and metal-air batteries [149], surface modifications are being investigated to enhance the surface area, ion transport kinetics, and stability of electrode materials. The use of advanced surface coatings, nanoscale architectures, and tailored surface functionalities can improve electrochemical performance and enable higher energy and power densities in these systems.…”
Section: Energy Applicationsmentioning
confidence: 99%